Acute and subchronic toxicity as well as evaluation of safety pharmacology of Galla chinensis solution. (13th March 2015) - Xiang, Fa; Peng, Lianci; Yin, Zhongqiong; Jia, Renyong; Hu, Zhiqiang; Li, Zhengwen; Ni, Xueqin; Liang, Xiaoxia; Li, Lixia; He, Changliang; Yin, Lizi; Su, Gang; et al.
Abstract: Galla chinensis has been popularly used in traditional Chinese medicine which is beneficial for the treatment of various diseases, such as inflammation, dysentery, toxicosis and sore. However, it has not previously been evaluated for safety through systematic toxicological studies. In the present study, acute and subchronic oral toxicity studies and safety pharmacology evaluation of Galla chinensis solution (GCS) were conducted in specific pathogen-free (SPF) Sprague–Dawley (SD) rats. Acute administration of GCS was done as single dose from 3333 mg to 6912 mg per kg/bodyweight (bw) and subchronic toxicity study for 30 days was done by daily oral administration of GCS at doses of 500, 1500 and 2500 mg/kg body weight in SPF SD rats. The acute toxicity study showed the LD50 of GCS was greater than 5000 mg/kg. The results of sunchronic toxicity study showed that the no-observed effect level of GCS was lesser than 1500 mg/kg bw day, which suggested three times higher than that of recommended dose for clinical applications (500 mg/kg bw day). The dose at 2500 mg/kg bw day of GCS may slow down the growth of rats and lead to degeneration and necrosis of tissue cells to some extent. In the safety pharmacology study, GCS did not produce any side effects to rats in central nervous system, cardiovascular system and respiratory system. Therefore, from the results of the study presented herein, it could be concluded that the use of appropriate levels (one to three times of recommended dose for clinical applications) of GCS as a topical preparations is considered safe. Graphical abstract: GCS had damages on liver, mainly detected as granular in cells and focal necrosis and karyorrhexis.